PERILAKU TEKAN KOMPOSIT LAMINASI KAYU â BAJA RINGAN DENGAN KONEKTOR GESER SEKRUP - , Kundari Rahmawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cold formed steel has large width-to-thick ratio so can buckling easily. Composite of timber lamina and cold formed steel would be solution for reducing local buckling under axial compression loading. This research is aimed to identify compressive strength and buckling behaviour of composite beam. Swietenia mahagoni and cold formed steel 75Z08 were used in this study. As shear connector, screws of 4 mm in diameter were used in composite beam specimens. There were 15 specimens of composite beam with 200 mm, 300 mm, 600 mm, 900 mm, and 1200 mm of buckling length (Lk). As comparison, three cold formed steel specimens of each buckling length were also tested under compression loading. The lateral deformation of the composite beam was measured by three LVDTs attached on the specimens during loading. Failure mode of timber lamina - cold formed steel composite was also observed. The result showed that local buckling would be reduced by combining cold formed steel with timber lamina. The composite system also enhanced the maximum compressive strength of cold formed steel. The maximum strength of composite beam increased around 6.7 times, 6.2 times, 4.7 times, 3.5 times and 3.0 times of cold formed steel respectively, for beam with buckling length (Lk) of 200 mm, 300 mm, 600 mm, 900 mm, and 1200 mm. Early failure of cold formed steel beam was local buckling on web section then followed by buckling on its flens. While composite beam, its failure mode was local buckling on its flens and also global buckling on its web due to its slenderness.